Temperature‐Dependent Modulation of the QRS Axis Following Water Intake in Healthy Adults: A Cross‐Sectional Study - Larry Atakora‐Amaniampong; Elsie Effah Kaufmann; Anderson Mon (Health Science Reports, 2026)
ABSTRACT Background and Aims Anecdotal concerns persist regarding the safety of cold and warm water ingestion and their impact on cardiac rhythms. This study aimed to investigate the acute effects of water temperature on QRS amplitude, duration, and axis in healthy individuals using electrocardiography (ECG). Methods A cross‐sectional study was conducted between January 2019 and October 2020 with 25 healthy volunteers (aged 18–35). Participanats ingested 250 mL of cold (0°C–8°C), room‐temperature (~27°C), and warm water (55°C–60°C) at 10‐min intervals. Simultaneous digital ECGs were recorded, with leads III, aVR, aVL, and aVF derived using Einthoven's laws. Data was analyzed using one‐way repeated measures ANOVA and Dunnett's post‐hoc analysis (). Results Statistics are reported as Mean ± SD ( n = 25). Warm water ingestion significantly decreased mean QRS amplitude in lead II (0.91 ± 0.09 to 0.86 ± 0.09 mV; p = 0.009), lead III (0.62 ± 0.09 to 0.52 ± 0.09 mV; p < 0.001), and lead aVF (0.73 ± 0.24 to 0.65 ± 0.24 mV; p < 0.001). Amplitude decreased by up to 16.3% (Lead III, warm water) and increased by 3.4% (Lead I, warm water). Cold water ingestion significantly decreased mean QRS duration from 92.1 ± 10.0 to 86.6 ± 10.0 ms ( p < 0.001). Warm water intake shifted the mean QRS axis from 62.3 ± 4.86° to 59.4 ± 4.86° ( p = 0.01), a 5° anticlockwise shift. Conclusion Water temperature acutely modulates ventricular depolarization, causing transient decreases in QRS amplitude, duration, and axis. These findings suggest internal thermal perturbations influence cardiac electrical orientation, likely due to the anatomical proximity of the gastrointestinal tract to the myocardium.